Strategy for Enhancing Productivity Using the Interpretive Structural Modelling (ISM) Method: Strategi Peningkatan Produktivitas dengan Metode Interpretive Structural Modelling (ISM) - Ramadhany, Muhammad Faizal Alfaini; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the application of Interpretive Structural Modeling (ISM) to enhance labor productivity in concrete manufacturing, specifically focusing on u-ditch products. The ISM method was selected for its simplicity and clarity in identifying critical elements that impact productivity. The research highlights the paramount importance of leadership commitment, which emerged as a level 1 variable, underscoring its role as a fundamental factor that must be prioritized. Findings suggest that addressing leadership commitment effectively leads to significant improvements in labor productivity. These results underscore the potential of targeted managerial interventions in boosting operational efficiency in industrial settings. Highlights : Leadership Commitment as the key element variable in increasing labor productivity through ISM. The simplicity and ease of understanding of ISM make it suitable for addressing critical aspects of U-Ditch concrete production. Focusing on the most important variables, such as leadership commitment, helps improve overall efficiency and effectiveness in the manufacturing process. Keywords - Interpretive Structural Modeling (ISM), Increased Productivity, key element